The Genealogy of Šemetas' in 15th-16th century - Saulė Viskantaitė-Saviščevienė (Lietuvos Istorijos Studijos)
The beginning of the Šemetas' kin is related to the middle of the 15th century when the ancestor of this family, Šemeta Nemeikaitis (the son of Nemeikis), was mentioned. He had 2 sons: Mikalojus and Jonas, who were descendants of 2 ramifications of the Šemetas' kin. It is unclear when and why the first (Jonas) offshoot was called by Šemetas' name. But at the beginning of the 16th century, Jurgis Jonaitis (Jurgis the son of Jonas) had this name as a surname. The earliest reference of Nemeikaičiai-Šemetas' family shows us that they were the relatives of Galiginas and his kin (Račkaičiai, Jackaičiai, Radaičiai, and Butkaičiai). The above-mentioned kin's main patrimonial domains were Voverys (nowadays Vaverka in Belarus). They were the offspring of Galiginas, who participated in the union of Horodlo in 1413 when he got the Polish coat of arms of Swan (Labędi). This armorial sign was saved and used by the kin of Galiginas. The Šemetas' family was closely related either by blood or marriage to noble kin like Kantautas, Chodkevičiai, Zavišos, Iljiničiai, and others. Finally, in the 16th century, the Šemetas' family moved their residence to Samogitia. The activity of the family men in public life started expanding when they began to live in Samogitia. Therefore, they had duties that were often closely related to this region. Merkelis Šemeta was the vice-prefect (Slavic - podstarosta, Latin - vice-capitaneus) of Samogitia. After that, he became the governor (tivun) of Palanga, Tendžiogala, and Beržėnai. Finally, he occupied the place of the castellan of Samogitia. He had a son, Vaclovas, who was the podkomorzy (the judge of land-ownership cases) of Samogitia. Later, he was the castellan of Polotsk and Smolensk. The second son, Merkelis, was the podkomorzy of Ukmergė and Vilnius and the magistrate of the treasury of the Grand Duchy of Lithuania (henceforth GDL). At first, Stanislovas, the brother of Merkelis, was vice-prefect of Telšiai, and after that, he became the governor of Pajūris. Eventually, he occupied the office of the GDL as a kuchmistrz (Lat. magister coquille). Merkelis Vaitiekaitis Šemeta was the marszalek (Lat. marszalcus) of the king and the governor of Dirvėnai. He inherited the latter office from his father Vaitiekus Jonaitis Šemeta. Merkelis Stanislovaitis Šemeta was the most famous from this kin in the political sphere. He was a member of the Liege Lords Council (rada panow). He was trustworthy because nobles confided in him to defend various interests against the sovereign. Moreover, the monarch appreciated Merkelis as a person, and he was appointed to edit the Second Lithuanian Statute. In 1569, M. Šemeta, together with other famous representatives of the GDL elite—the Lithuanian liege lords—were participants in the Parliament (Sejm) of Lublin when the project of the union was discussed. The middle of the 16th century was the biggest culmination of the Reformation. Most noblemen of the GDL, including the Šemetai, corresponded very intensively with Duke Albrecht, who was a resident of Prussia. Duke Albrecht advised urgently to send their children to foreign countries for studies (mostly to Germany, which was the cradle of Protestantism). Therefore, when the new religion spread, it was needed to support at first Lutheran and later Calvinistic communities and churches. In the region of Samogitia, the Šemetai distinguished themselves as diligent protectors and supporters of the Reformation. It is certainly true that brothers Jonas and Vaclovas Šemetas belonged to the local elite of the GDL and took an active part in the Reformation movement. It is supposed that in 1567, Merkelis (succeeded by his son Jonas) was the person who took care of and supported the Lithuanian Lutheran School in Tauragė. Jonas and Vaclovas had received a good education at Leipzig University. They were interested in the accumulation of books in their private libraries and communicated with highbrows of that time. It is possible that they were associated with the well-known intellectual, historian, and annalist Maciej Stryjkowski.